NATRIUM DALAM DARAH TENAGA KERJA SEBELUM DAN SESUDAH TERPAPAR PANAS (STUDI KASUS DI BAGIAN BUFFING PROCESS PT YAMAHA MUSICAL PRODUCTS INDONESIA PASURUAN TAHUN 2015) - Vebrin Arsintha Tungga Dewi; Demes Nurmayanti; Ngadino . (GEMA LINGKUNGAN KESEHATAN, 2016)
Excessive exposure to heat resulting heat cramps, heat exhaustion and heat stroke. Workers who have not been acclimatized to hot temperatures are usually sweat more than usual. In this condition, human will lose body fluids and electrolytes. The purpose of this study analyzes the differences of sodium level in the blood of workers before and after exposure to heat.This is an observational analytic research with cross sectional approach. Data was obtained from the measurement result with total population of 15 workers and sample of 14 workers. The data was analyzed analytically by using Paired Sample T Test..The results shows that all workers aged less than 40 years with working period of less than five years and most of whom indicated normal nutritional status. The company has conducted engineering controls, administrative and PPE. P value was ≤ 0.01 and result of paired t test revealed highly significant.The Conclusion underlines difference in the level of sodium in workers’ blood before and after exposure to heat for 2.5 hours.Installation of local exhaust ventilation as well as the training of labor on heat stress and prevention is suggested.